The search for delicious - Babbitt, Natalie (New York : Farrar, Straus and Giroux, 1985)
The Prime Minister is compiling a dictionary and when no one at court can agree on the meaning of delicious, the King sends his twelve-year-old messenger to poll the country.
"A Sunburst book."
910
Accelerated Reader AR
Keywords: Fantasy fiction